2016
DOI: 10.1515/yplm-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the effect of systemic functional linguistics applied through a genre-pedagogy approach to teaching writing

Abstract: In the tradition of teaching English as a second language, there has been an increased interest in how functional language descriptions and understandings of genres may be used as resources for making meaning. The present study investigates what impact writing instruction that draws upon systemic functional linguistics (SFL) applied through a genre-pedagogy approach has on students' ability to write argumentative essays. This includes explicit grammar instruction inspired by SFL, as well as instruction on text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…The students starting in upper secondary school come from a tradition where writing texts with involvement and using a personal style has been encouraged (Øgreid & Hertzberg, 2009, p. 458). Interviews carried out to follow up on the current study indicate that the students had not learnt much about writing argumentative texts and using formal language before upper secondary school (Horverak, 2016b). Keeping this in mind, it is not surprising that the students struggle when met with totally different expectations in upper secondary school.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The students starting in upper secondary school come from a tradition where writing texts with involvement and using a personal style has been encouraged (Øgreid & Hertzberg, 2009, p. 458). Interviews carried out to follow up on the current study indicate that the students had not learnt much about writing argumentative texts and using formal language before upper secondary school (Horverak, 2016b). Keeping this in mind, it is not surprising that the students struggle when met with totally different expectations in upper secondary school.…”
Section: Discussionmentioning
confidence: 70%
“…The current study focuses on a dataset collected during a quasi-experimental study that tested out the effects of a genre-pedagogical approach to teaching argumentative writing in English in an ESL (English as a second language) context in upper secondary school (Horverak, 2016a). The results of this study showed that students improved from pre-to posttests regardless of first language, gender and what grade they had been given in English previously.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that increasing teachers’ understanding of functional linguistics had a positive effect on their instruction of language in content areas. Similarly, Horverak (2016) explored the impact of writing instruction informed by systemic functional linguistics on students’ writing skills in Norwegian upper secondary schools. The findings revealed that explicit grammar instruction with an SFL perspective can improve students’ essay writing skills.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…In the process of English graduation thesis writing, there are some differences between the students' knowledge level, the ability to analyze and solve problems [7]. In the actual process of writing, there are some problems such as inappropriate selection of topics, vocabulary selection, errors in grammatical application, irregular format and insufficient reference to foreign materials [8].…”
Section: Problems In English Graduation Thesismentioning
confidence: 99%